Filipino Catholics in Japan and ambiguity of 'full integration' - Macaraan, Willard Enrique R. (Animo Repository, 2017)
Utilizing Wacquant's theorization of urban ghetto, this paper argues based on a field study of selected churches in the Archdiocese of Tokyo that the negotiated existence of Filipino Catholics in Japan, at least in the Archdiocese, has shifted from being a "sworded victim" to being a "shielded enclave." In response to aging demographics and increasing nonreligiosity of the young, the Archdiocese initiated a vision of "full integration," generally understood as a strategic goal to achieve an image of a multicultural Church that implies a call to end any dynamics of "swording" on the part of the dominant group as well as "shielding" among the subordinated ones. In deconstructing the ambiguity of "full integration," the paper analyses traces and cues provided by the Filipino Catholics' negotiated existence in the Archdiocese of Tokyo. In addition, the paper makes use of ideations from Will Kymlicka's bi-partite multicultural theory, which may be helpful in articulating a solution to the ambiguity of "full integration" as well as to the predicament of disinterested bicultural youth of the Church in Japan. © 2017 Journal of Dharma: Dharmaram Journal of Religions and Philosophies (DVK, Bangalore),.